Knowledge co-creation in Open Innovation Digital Platforms: processes, tools and services. Issue 7 (5th August 2019) - Abbate, Tindara; Codini, Anna Paola; Aquilani, Barbara
Abstract : Purpose: The purpose of this paper is to understand how Open Innovation Digital Platforms (OIDPs) can facilitate and support knowledge co-creation in Open Innovation (OI) processes. Specifically, it intends to investigate the contribution of OIDPs-oriented to successfully implement all the phases of interactive coupled OI processes. Design/methodology/approach: The paper carries out an exploratory qualitative analysis, adopting the single case study method. The case here investigated is Open Innovation Platform Regione Lombardia (OIPRL). Findings: The case study sheds light on how OIPRL supports knowledge co-creation through its processes, tools and services as a co-creator intermediary. In its launch stage, the platform simply aimed at giving firms a tool to "find partners" and financial resources to achieve innovative projects. Now, however, the platform has developed into an engagement platform for knowledge co-creation. Research limitations/implications: One limitation lies in the particular perspective used to perform the case study: the perspective of the digital platform itself. Future research should focus on the individuals engaged in the platform to better investigate the processes, tools and services used to implement the OI approach. Practical implications: The paper suggests ways in which OIDPs could be used by firms for effective exploration, acquisition, integration and development of valuable knowledge. Originality/value: The study conceptualizes the role of OIDPs in shaping knowledge co-creation, assuming that the platforms act as Open Innovation Intermediaries (OIIs). Specifically, OIDPs can be observed to function as "co-creator intermediaries" that define, develop and implement dedicated processes, specific tools and appropriate services for supporting knowledge co-creation activities.